2007
DOI: 10.1373/clinchem.2007.091363
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Technical Analysis of Urine RNA-Based Tumor Diagnostics Reveals ETS2/Urokinase Plasminogen Activator to Be a Novel Marker for Bladder Cancer

Abstract: Background:The noninvasive detection of RNA tumor markers in body fluids represents an attractive diagnostic option, but diagnostic performance of tissue-derived markers is often poorer when measured in body fluids rather than in tumors. We aimed to develop a procedure for measurement of tumor RNA in urine that would minimize donor-dependent influences on the results. Methods: RNA isolated from urinary cell pellet, celldepleted fraction, and whole urine was quantified by reverse transcription quantitative-PCR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 31 publications
2
26
0
3
Order By: Relevance
“…In consequence, the analytical focus on sediments as done in several studies does not let expect satisfying results. A similar phenomenon of differences between samples of whole urine, cell-depleted urine, and sediments was also observed in bladder cancer patients for various mRNAs [9]. In addition, the differences in that study were not uniform for all tested mRNAs but showed a particular behavior for specific mRNAs [9].…”
supporting
confidence: 70%
See 1 more Smart Citation
“…In consequence, the analytical focus on sediments as done in several studies does not let expect satisfying results. A similar phenomenon of differences between samples of whole urine, cell-depleted urine, and sediments was also observed in bladder cancer patients for various mRNAs [9]. In addition, the differences in that study were not uniform for all tested mRNAs but showed a particular behavior for specific mRNAs [9].…”
supporting
confidence: 70%
“…A similar phenomenon of differences between samples of whole urine, cell-depleted urine, and sediments was also observed in bladder cancer patients for various mRNAs [9]. In addition, the differences in that study were not uniform for all tested mRNAs but showed a particular behavior for specific mRNAs [9]. Thus, the focus on possible new urinary markers including noncoding nucleic acids like microRNAs, long non-coding RNAs, and piRNAs should draw attention to this aspect.…”
supporting
confidence: 62%
“…55 Hypermethylation of the caveolin-1 gene and abnormal caveolin-1 protein expression have crucial roles in cell differentiation and in the phonotypical conversion of TCC into nonurothelial carcinomas. 56 Among the transcription factors that were studied at promoter pull-down analysis with the nuclear extract from murine sham and PBOO BSM tissues, transcription factor Ets-2 is overexpressed in human bladder cancer, 57 and SP-1 regulates tumor necrosis factor-␣-induced MMP-9 expression through ERK1/2 and p38 MAP kinase in bladder cancer cells. 58 However, in murine and human obstructed BSM tissues, Ets-2 and SP-1 are not overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…However, in urine we can found a significant amounts of cell-free RNA and for this reason RNA tumor markers (e.g., hTERT, UPK1A, HTATIP2), cannot be used unconditionally for RT-qPCR-based analysis of whole urine [97]. Another system that has been intensively studied for its role in tumorigenesis is uPA: ETS2.…”
Section: Rna Messengermentioning
confidence: 99%
“…In the case of bladder cancer higher ETS2 RNA concentration it is observed compared with uPA. This tumor marker ratio of ETS2: uPA could be an interesting diagnostic tool [97][98][99][100][101]. Hedegaard et al prepared a total RNA-sequencing (RNA-seq) libraries for 476 patients with bladder cancer at different stages (Ta, T1, in situ [CIS], MIBC).…”
Section: Rna Messengermentioning
confidence: 99%